Thai Nurses' Learning Needs Regarding Disaster Nursing: High Needs? - Phakdeechanuan, Kirana; Songwathana, Praneed; Sae-Sia, Wipa (Department of Nursing, Faculty of Medicine, Diponegoro University, 2015)
Background: Disaster nursing has become a critical concern, worldwide, due to a trend toward management strategy. However, limited studies are conducted in Thailand where nurses have faced increasing threat to both natural and man-made disasters.Purpose: To describe the amounts of learning needs (both expressed and normative needs) regarding disaster nursing among Thai nurses.Methods: The sample included 454 registered nurses who have been working inThailand for at least six months selected through the multi-stage sampling methods. Data were collected using questionnaire included the Learning Needs Regarding Disaster Nursing Questionnaire (LNDNQ), developed based on the learning needs triangle model and the concept the International Council of Nurses (ICN) Framework of Disaster Nursing Competencies. The LNDNQ was tested for content validity by three experts and for reliability with 20 nurses using Cronbach’s alpha coefficient yielding a value of .97 (expressed needs), and .99 (normative needs), respectively. Data were analyzed by descriptive statistics.Result: This study found that the top three contents of the most learning needs in expressed needs were similarly with the most normative needs which items were related to mitigation/prevention and response phase. The most learning needs they expressed were assisting and first aid for victims at the scene (n=229, 50.4%), followed by basic principle of triage (n=218, 48.0%), and training of the disaster nursing management plans (n=217, 47.80%). However, the top least expressed needs were related to mitigation/prevention and recovery/rehabilitation phase. These were providing an information for community with the notification, and announcement the severity level of disaster (n=32, 7.0%), followed by preparing and organizing the evacuation area for victims (n=37, 8.1%).Conclusion: The contents related to the most learning needs (expressed needs andnormative needs) regarding disaster nursing must be emphasized in training course and nursing curriculums in Thailand to improve Thai nurses' capability in disaster nursing management.